Transitioning to a low-carbon Irish economy: An analysis of regional labour impacts - Kelly C. De Bruin; Martina Lawless; Eoin Monaghan; Aykut Mert Yakut (The Economic and Social Research Institute (ESRI), 2019)
This report analyses the county-level impacts of increasing the carbon tax and gradually phasing out peat and coal from electricity production.
Keywords: 330